Infectiological, functional, and radiographic outcome after revision for prosthetic hip infection according to a strict algorithm - De Man, F Harald R; Sendi, Parham; Zimmerli, Werner; Maurer, Thomas B; Ochsner, Peter E; Ilchmann, Thomas (Acta orthopaedica, 2011)
Background and purpose Successful treatment of prosthetic hip joint infection (PI) means elimination of infection and restored hip function. However, functional outcome is rarely studied. We analyzed the outcome of the strict use of a treatment algorithm for PI. Patients and methods The study groups included 22 hips with 1-stage exchange for PI (group 1), 22 matched hips revised for aseptic loosening (controls), and 50 hips with 2-stage exchange (group 2). Relapse of infection, Harris hip score (HHS), limping, use of crutches, reoperations, complications, and radiographic changes were compared between the groups. Results There was 1 relapse of infection, which occurred in group 2. In group 1, the mean HHS was 84; 4 of 19 patients were limping and 2 required 2 crutches, which was similar to the control results. In group 2, scores were lower and complication rates higher. The use of a Burch-Schneider ring and the presence of a deficient trochanter impaired function. There were no differences in radiographic outcome between the groups. Interpretation With the algorithm used, infection can be cured with high reliability. With a 1-stage procedure, mobility is maintained. After 2-stage procedures, function was impaired due to there being more previous surgery and more serious infection.